Large genomic rearrangements in the CFTR gene contribute to CBAVD - Guittard Caroline; Girardet Anne; Taulan Magali; Altieri Jean-Pierre; Templin Carine; Beroud Christophe; des Georges Marie; Claustres Mireille (BMC, 2007)
Abstract Background By performing extensive scanning of whole coding and flanking sequences of the CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) gene, we had previously identified point mutations in 167 out of 182 (91.7%) males with isolated congenital bilateral absence of the vas deferens (CBAVD). Conventional PCR-based methods of mutation analysis do not detect gross DNA lesions. In this study, we looked for large rearrangements within the whole CFTR locus in the 32 CBAVD patients with only one or no mutation. Methods We developed a semi-quantitative fluorescent PCR assay (SQF-PCR), which relies on the comparison of the fluorescent profiles of multiplex PCR fragments obtained from different DNA samples. We confirmed the gross alterations by junction fragment amplification and identified their breakpoints by direct sequencing. Results We detected two large genomic heterozygous deletions, one encompassing exon 2 (c.54-5811_c.164+2186del8108ins182) [or CFTRdele2], the other removing exons 22 to 24 (c.3964-3890_c.4443+3143del9454ins5) [or CFTRdele 22_24], in two males carrying a typical CBAVD mutation on the other parental CFTR allele. We present the first bioinformatic tool for exon phasing of the CFTR gene, which can help to rename the exons and the nomenclature of small mutations according to international recommendations and to predict the consequence of large rearrangements on the open reading frame. Conclusion Identification of large rearrangements further expands the CFTR mutational spectrum in CBAVD and should now be systematically investigated. We have designed a simple test to specifically detect the presence or absence of the two rearrangements identified in this study.